Production of Σ(1385)± and Ξ(1530)0 in p-Pb collisions at sNN=5.02 TeV - Adamová, D; Aggarwal, M M; Aglieri Rinella, G; Agnello, M; Agrawal, N; Ahammed, Z; Ahmad, S; Ahn, S U; Aiola, S; Akindinov, A; Alam, S N; Albuquerque, D S D; et al. (The European physical journal. C, Particles and fields, 2017)
The transverse momentum distributions of the strange and double-strange hyperon resonances (Σ(1385)±, Ξ(1530)0) produced in p-Pb collisions at sNN=5.02 TeV were measured in the rapidity range -0.5<yCMS<0 for event classes corresponding to different charged-particle multiplicity densities, ⟨dNch/dηlab⟩. The mean transverse momentum values are presented as a function of ⟨dNch/dηlab⟩, as well as a function of the particle masses and compared with previous results on hyperon production. The integrated yield ratios of excited to ground-state hyperons are constant as a function of ⟨dNch/dηlab⟩. The equivalent ratios to pions exhibit an increase with ⟨dNch/dηlab⟩, depending on their strangeness content.